Literatura kaszubska w perspektywie antropologii kulturowej - Kuik-Kalinowska, Adela (Slavia Occidentalis, 2013)
The areas of cultural anthropology covered in studies on Kashubian literature indicate the diversity of the issues dealt with in this work. The raising of ethnic consciousness is driven by a strong relationship with nature, and at the same time influences the perception of what is individual and what is shared. As seen through anthropological research on Kashubian literature, artistic representations of the imaginative world of Kashubia are complementary to the issues of cultural identity in its individual and collective formation. Through description of its subjects and themes it is possible to shed light on the image of Kashubian cultural reality, and the existential, spiritual and social image of Kashubian community life. Kashubians, in the literary image oservobservable from the anthropological perspective, are an ethnic group who speak their own language, nurture their own cultural identity and traditions, and also support a relationship to past and contemporary European culture.